Sineger Tengah and Kaca-kaca as The Deep-Structure of Sundanese Architecture in Pasundan Land, West Java, Indonesia - Salura, Purnama; ., .; ., . (International Journal of Engineering and Technology, 2018)
The remaining relics of Sundanese Architecture in the land of Pasundan, West Java Indonesia is relatively nonexistent. Until now a com-plete and in-depth research on Sundanese architecture is hard to find. This research raised the issue of the relation between concept of forms and concept of meaning of Sundanese society in the Kampongs Dukuh, Ciherang and Palasah. These three kampongs are kam-pongs that still practiced the Sundanese customs and could represent Sundanese architecture in the land of Pasundan. The purpose of this study is to uncover and opened all the relationships that are intertwined in architectural forms and architectural meaning of the Sundanese community in three cases of study. This study is descriptive-analytical and interpretative which is based on a combination of typological approach along with structuralism approach in architecture. Through thorough analysis, the research has revealed that the concept of Sineger-tengah and Kaca-kaca served as a deep-structure that influenced the Sundanese architecture in three cases study. While the bene-fits obtained are : firstly, the research succeeded in formulating a new reading tool that could be used to read the relationship between form and meaning of Sundanese architecture. Secondly, the research could be used as a reference for the survival strategy of the Sun-danese society in the context of the influence of global change. Thirdly, the research could be used as a starting point for the development of new architectural theories in Indonesia in particular, which indirectly could affect the global architectural theories in general